2020
DOI: 10.1007/s00709-020-01536-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the duration of use of aluminum cookware on its metal leachability and cytogenotoxicity in Allium cepa assay

Abstract: Aluminum cookware are widely used in many parts of the world. Data is increasing on the leaching of toxic metals from aluminum cookware into food and drink. In the present study, cytogenotoxicity of water boiled in three different aluminum pots (new, 3-year-old, and 6-year-old) in onion root tip's dividing cells was evaluated using the Allium cepa assay. The concentrations of Pb, As, Cd, Cu, Ni, and Al in the samples were also analyzed. Onion bulbs were grown in the boiled water samples, while tap water serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The human environment is broadly polluted with aluminum (Al), the third most abundant element in the Earth’s crust, frequently found in combination with oxygen and other elements in bedrocks, soil, and sediments [ 1 ]. It is known for use in the production of household items, pans, packaging, construction, and transportation [ 2 ]; next, Al is used for vaccines manufacturing, where it performs the function of adjuvant to stabilize and preserve them [ 3 ] and also in the process of water treatment for removal of particulate materials [ 4 ]. Its exposure can be environmentally associated with acid rain, due to its high solubility capacity in acidic environments, and ultimately can lead to high levels of Al in plants, spices, cereals, vegetables, or grains, which can later be used for food products such as teas, food additives, coffee or granular products [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The human environment is broadly polluted with aluminum (Al), the third most abundant element in the Earth’s crust, frequently found in combination with oxygen and other elements in bedrocks, soil, and sediments [ 1 ]. It is known for use in the production of household items, pans, packaging, construction, and transportation [ 2 ]; next, Al is used for vaccines manufacturing, where it performs the function of adjuvant to stabilize and preserve them [ 3 ] and also in the process of water treatment for removal of particulate materials [ 4 ]. Its exposure can be environmentally associated with acid rain, due to its high solubility capacity in acidic environments, and ultimately can lead to high levels of Al in plants, spices, cereals, vegetables, or grains, which can later be used for food products such as teas, food additives, coffee or granular products [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that even at low temperatures, there is a risk of metal exposure. This could be attributed the manufacturing defects [26] and the scrap metals which are used as raw materials [48]. At 150˚C and 200˚C, aluminium cookware leached Pb (4.00 ± 0.30 × 10 −2 mg/ml), Al (72.90 ± 0.08 × 10 −2 mg/ml) and Cr (13.20 ± 0.34 × 10 −2 mg/ml) with concentration above WHO permissible limits (Table 4).…”
Section: Effect Of Temperature On Leaching Of Metals From Different C...mentioning
confidence: 99%
“…In this study, the leaching of aluminum pot and other pots at the different pHs were done using the same pot with deionised water after each other.This process must have inhibited the leaching of aluminum. However, Alabi et al, [21] found that when water was boiled in new aluminum pots for 1 hour it leached 0.023 mg/L of aluminum. While three year old pressed aluminum pots leached 0.029 mg/L and 6 years old aluminum pots leached 0.048 mg/L of aluminum.…”
Section: Effect Of Ph On the Amount Of Ptms Leached From Glassmentioning
confidence: 99%
“…Previous researches conducted on the leaching of metals from different cook wares used specific food in their studies such as tomatoes sauce [15,17], fish stew [12], 3% acetic acid solution [11], rice [13], vegetables [18], fruit juices [19], beans [20], except Lar et al, [16], Alabi et al, [21] Alabi and Adeoluwa, [22] and Noemie et al [17] used water. With food substances, parameters such as pH cannot be easily monitored or varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation